Working the Body: ethical relations in the construction of the self and the collective - Vilene Moehlecke; Tania Mara Galli Fonseca; Andréia Machado Oliveira (Educação & Realidade, 2013)
The present article looks at ways that the self and the collective are constructed with in labour relations. These relations have been found to espouse positions that oscillate between a Spinozist Ethicswhich empowers bodies and a morality which imprisons them. We posit that increasing the potential of bodies entails the augmentation of relationalpossibility, i.e. the activation of unused potentials of being disclaimedby majoritary practice. Our approach which looks at the interaction between relational bodies, work and ethics finds support in Spinoza, Deleuze and Schwarz among others. We propose to undertake a construction of individual and collective action to generate dispositive for analyzing and modifying relational processes in the workplace.